Training on Creating Batik Stamps from Paper Waste and Innovation in Its Application to Shibori Cloth for Teachers and Students of High School and MA in Bantul - Muhajirin, Muhajirin; Mahardhika, Cholis; Pahlawan, Reza (Jurnal Abdimas, 2025)
This summarizes the implementation of a training program aimed at enhancing teachers’ competencies in utilizing paper waste as an innovative and sustainable teaching media. The activity commenced with thorough preparation, including the development of training materials, tools, and practical supplies, as well as preparing discussion and evaluation facilities. The implementation involved lectures, live demonstrations, interactive discussions, and independent hands-on practice, with close supervision from the team of instructors. Participants not only gained theoretical knowledge but also practical experience in creating handprinted textiles from paper waste. Ongoing mentorship was provided to ensure the application of the training results in school environments and to support the continuous development of innovative and eco-friendly creations. Through an interactive approach and direct practice, this activity successfully improved participants’ skills in producing environmentally friendly craftworks and fostered awareness of creative waste management. The outcomes of this training are expected to enrich teachers’ competencies and increase awareness of environmentally responsible innovations. Overall, this program contributed positively to the development of craft education and environmental sustainability, opening opportunities for similar activities to be implemented more broadly and sustainably in the future.